The World as God’s Property in Psalm 24:1-2 as the Source of Man’s Right Attitude Towards Creation - Nawrot, Janusz (Studia Ecologiae et Bioethicae, 2023)
The ongoing discussion on various forums regarding human responsibility for the ecological state of the surrounding world, should include the voice of the word spoken in the Bible by God, the Creator of heaven and earth. For believers, this very voice has a decisive power, however, it has been neglected for so long and the effects that can be seen with the naked eye. The binding power of this word can become an important argument in that discussion and catalyst for actions in the area of environmental protection, to which Pope Francis draws so much attention. This paper joins the unanimous choir of nature defenders, and it aims at drawing the reader’s attention to selected aspects of human relationship with the world, presented in the opening verses of Psalm 24. The passages provide a clear testimony to the biblical authors’ awareness of both the dependence of the world - including man - on its Creator, and the essential moral implications of that fact. It may help us realize our responsibility for the world around us as well as the necessity to react whenever the positive interaction between man and the environment is at risk. That is how, the beauty and richness of creation can become a path to God, its Creator.